Development of flood hazard map for Johor river basin / Noor Farahain Muhammad Amin - Noor Farahain, Muhammad Amin (2017)
Over many parts of the world, the large-scale atmospheric circulations and anomalies have been shown to have a significant impact on seasonal weather. Malaysia with seasonal monsoons of Southwest and Northeast Monsoons is located in the South East Asia. In December 2006 and January 2007, the Northeast Monsoon had brings heavy rain through series of continuous extreme storms that caused a devastating floods in the northern region of Peninsular Malaysia particularly to Kota Tinggi, Johor. The storms had occurred in two separate phases in late December 2006 and early January 2007 with a total precipitation in four days exceeding twice of the monthly rainfall in which some places recorded a higher number. The 2006 average rainfall return period is 50-years while the later gave more than 100-years return period. The disaster had caused more than 100,000 people evacuated from the residents due to rising flood water. The 2006 flood depth is recorded as 2.3 m and the 2007 flood depth is given as 2.75 m. Flood hazard maps allows quantification of what is at risk of being flooded, such as the number of houses or businesses. This helps to identify the scale of emergency and clean-up operations. The creation of flood hazard maps in give the information for the area prone to the flood should promote greater awareness of the risk of flooding. The objectives of this study are to develop a river model for Johor River by using InfoWorks RS for future prediction and simulation, and to produce the flood hazard map for Johor River Basin. The river modeling of Johor River has been done using InfoWorks RS software. 147 cross-sections have been used to model Johor River. The manning coefficient, n was used the method of trial and error then determined to be in range of 0.035 to 0.20. Results from the modeling indicated water surface profiles that showed river bank overflows along with some of the parameters such as flow, water level, and velocity for 50 and 100 ARI along Johor River. The flood hazard map had generated using 1-D and 2-D modeling. 2-D modeling flood hazard map has obtained and the velocity variation and also the flow direction included in these flood hazard map. Combined or hybrid 1-D and 2-D modeling is now and the way forward in river and flood modeling. By using 1-D simulation to identify location of flooding and 2-D to investigate direction and depth of flood flows in specific areas.